Comparative Study of Preservation Methods for Berberis Lycium Juice: A Laboratory Approach at Shaheed Benazir Bhutto University, Sheringal, Dir Upper, Pakistan - Aziz Un Nabi; Atta Ullah; Gul, Jaweria; Abdullah; Siab, Muhammad (Indus Journal of Bioscience Research, 2024)
This study examines the effects of diverse preservation techniques on the shelf life, nutritional importance, microbiological safety, and sensory behavior of Berberis lycium juice. These techniques consist of vacuum sealing, freezing, refrigeration, and adding natural preservatives such as sugar and honey. Berries were harvested from Pakistan’s Upper Dir highlands and turned into juice in a lab. Samples were stored and examined using each technique at intervals of 7, 10, 13, 16, 19, 21, 24, 27, and 30 days. Microscopy was used to inspect microbial development, and other parameters like pH, TSS, ascorbic acid concentration, microbial load, and sensory attributes were assessed. For long-standing preservation, vacuum sealing and refrigeration were not as much of successful as freezing, which deeply enhanced microbiological safety and sensory quality, predominantly when paired with honey or sugar. Three days passed previous to the control sample going bad. The study concludes that the best way to preserve Berberis lycium juice is by freezing it with natural preservatives. An evergreen plant aboriginal to the Himalayan region, Berberis lycium belongs to the Berberidaceae family. It has long been utilized for food and medicine, as well as for its roots, bark, stems, leaves, and fruits. The plant is well-identified in Ayurvedic medicine for its capability to prevent harm to the liver, abdomen, skin, cough, and eyes. Pharmacological research highlights its hepatoprotective, anticarcinogenic, antipyretic, hypoglycemic, and hyperlipidemic characteristics. The fruits which are consumed in raw or processed into juices, jams, and preserves by local communities, are profuse in vitamins, minerals, antioxidants, and anthocyanins. An impression of the plant’s many qualities is the target of this paper. Berberis lycium and other plants take action as biosynthetic laboratories for substances that are superior for human health. Medicinal plant extracts habitually exhibit antibacterial action, productively preventing the enlargement of bacteria and fungi.